The first reports of patients with suicide ideas and attempts seen at a Psychosocial Care Center (Research, Society and Development, 2024)
This work aims to identify the context and biopsychosocial dimensions related to suicide ideation and attempts in patients who received their first care at a Psychosocial Care Center (CAPS), in the city of Palmas, Tocantins. This is documentary, retrospective research with a quantitative and qualitative approach. The object of this study were the records of the first service, contained in the service's “reception form”, with complaints of suicidal ideation and/or attempt in the year 2022. With the analysis of the records, we found that the majority of these were of female people, aged between 18 and 28 years, with education between complete secondary education and incomplete higher education. We observed the presence of a history of mental suffering in the family, and the categories that were most repeated were: anxiety, suicide ideation and attempts, crying, family conflicts and violence in the family environment. In this study, it was observed that suicide ideation and attempts occurred in younger people than reported in other studies. We conclude that genetic factors and socio-family relationships have a direct relationship with mental suffering and the desire for self-extermination.